PENGARUH LEADER MEMBER EXCHANGE (LMX) DAN REWARD SERTA PUNISHMENT TERHADAP KINERJA KARYAWAN (Studi Pada PT. Asuransi Umum Bumiputera Muda Samarinda) - Shinta Andini Dewi Putri; Djoko Setyadi; Dirga Lestari AS (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2019)
Shinta Andini Dewi Putri, 2018, The influence of Leader Member Exchange (LMX), Reward, and Punishment toward Employee Performance at PT. Bumiputera Muda General Insurance Samarinda. Faculty of Economics and Business Mulawarman University under the guidance of Prof. Dr. Djoko Setyadi, SE., M.Sc and Dr. Dirga Lestari AS, SE., MM. The purpose of this study is to determine the effect of Leader Member Exchange (LMX), Reward, and Punishment to Employee Performance at PT. Bumiputera Muda General Insurance Samarinda. Determination of the sample in this study was carried out with non probability sampling. Sample taken by 40 employees of PT. Asuransi Bumiputera Muda General Insurance Samarinda. Sampling method with saturated sampling procedures, all of whice are respondents in this study. This study uses primary data obtained by distributing questionnaires to employees working at PT. Bumiputera Muda General Insurance Samarinda. Data analysis technique used in this study is multiple linier regression using SPSS 23 program. The results showed that the Leader Member Exchange (LMX), Reward, and Punishment has a positive and significant effect on employee performance of PT. Bumiputera Muda General Insurance Samarinda.